A dual-channel colorimetric and fluorescent sensor for the rapid and ultrasensitive detection of kanamycin based on gold nanoparticles-copper nanoclusters. Issue 48 (1st December 2021) - Nie, Qi; Deng, Jingjing; Xie, Bing; Shi, Guoyue; Zhou, Tianshu
Abstract : The assay based on Au NPs-Cu NCs showed selective response toward kanamycin within 2 minutes with a low LOD of 1.9/1.2 nM. The sensor possesses good reliability and accuracy, and can be applied for kanamycin detection in environmental water samples. Abstract : In this work, a dual-channel assay was constructed for the colorimetric and fluorescent detection of kanamycin (KAN) based on gold nanoparticles (Au NPs) and copper nanoclusters (Cu NCs). Initially, the fluorescence of Cu NCs was quenched by 4-amino-3-hydrazino-5-mercapto-1, 2, 4-triazole (AHMT)-functionalized Au NPs due to the inner filter effect (IFE). The existence of KAN acted as a molecular bridge to interact with AHMT via hydrogen bonds and induced the aggregation of AHMT-Au NPs, leading to a change in the color of the gold colloidal solution from reddish-violet to blue within 2 min. Moreover, the aggregated AHMT-Au NPs can weaken its IFE toward Cu NCs and result in fluorescence restoration. With the sensor employed here, the concentration of KAN can be quantitatively analyzed through double channels, and a low LOD (limit of detection) of 1.9 nM and 1.2 nM was realized by the colorimetric and fluorescent method, respectively. Benefitting from the short response time, high sensitivity, and good reliability, the established assay offered great opportunities for the on-site monitoring of antibiotics in environmental samples.